In Vitro Antioxidant Activity of Zingiber officinale, Piper retrofractum, and Their Combinations - Wasito, Hendri; Ekowati, Heny; Hayati, Fitri Fauziah (Indonesian Research Gateway, 2011)
Many plants are used empirically as antioxidant. Plants that are frequently used in Indonesian communities are Zingiber officinale and Piper retrofractum. The aim of this research was to investigate the in vitro antioxidant activity of single ethanolic extract and the combinations ofZ. officinale and P. retrofratum using free radical scavenging DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Z. officinale and P. retrofratum were extracted by maceration using 95% ethanol for 3 x 24 hours. Antioxidant activity was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The concentration of the extract (μg/mL) that was required to scavenge 50% of free radicals (IC50)was calculatedusing the percent scavenging activities of six different extract concentrations. The results showed that the single ethanolic extract of Z. Officinalle produced the highest antioxidant activity with IC50of 56 μg/mL, while the antioxidant activity of the single ethanolic extract of P. retrofractum produced an IC50 of 3.445 μg/mL. The IC50 of combination of Z. officinale and P. retrofratum ethanolic extracts at concentration ratios of 1: 2, 1 : 1, and 2 : 1 were 148 μg/mL, 85 μg/mL, and 73 μg/mL.Key words: Zingiber officinale, Piper retrfratum, Antioxidant, DPPH